PATHOGENETIC CONNECTION OF INFLAMMATORY DISEASES OF THE PERIODONT WITH AVAILABILITY OF BACKGROUND SOMATIC PATHOLOGY - Rizaev, E.A.; Bekzhanova, O.E. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
It has been established that in various diseases of organs and systems functional and morphological changes occur in periodontal tissues, pathogenetic associated with the presence of background somatic pathology, which determines the more severe periodontitis. This is expressed by impaired metabolism, hemodynamics, immunological and neuroregulatory disorders, shifts in microbiocenosis, blood circulation occur, sensitivity of nerve endings changes, immunity disorders are detected, aggressive bacterial invasion is detected. There is a decrease in the regenerative capacity of oral tissues and impaired metabolism of the periodontal complex tissues, which creates conditions for the development of superinfection, leading to severe forms of periodontal disease with rapidly increasing tooth mobility, clinically and radiographically detected by a sharp loss of bone. In this regard, there is a need for complex treatment of somatic and dental diseases.